(untitled) (Global Journal of Computer Science and Technology, 2016)
Electronic Passport (e-passport) is one of the results of the electronic revolution in the World; since the passport is the document of the person in terms of identity and nationality and is the property of the country. One of the most important challenges is to protect this document from forgery. The common forgery for the passport is replacing its holder photo. The proposed system concentrates on the security part of the e-passport. It consists of two parts; the first part is hiding of the security code by using steganography and storing the same code in the RFID tag by the issuing country of the epassport. The other part will be operated at the control point of the destination country to make sure of the e-passport validity by checking the hidden code using NFC and verify it with the one in the RFID tag. If the two values are equal, then the system will compute a key using Diffie-Hellman Key Exchange. This key will be used to read the secret information in the tag.